AQUIRING OF A COMPANY’S OWN EQUITY INTEREST THROUGH REDEMPTION OF A COMPANY MEMBER - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
A company’s own equity interest is an equity interest acquired from one of its members. It possible for a company to acquire a whole or a part of an equity interest of its member. There are different legal situations and modes in which a company can acquire an equity interest from its members. It is possible for a company to acquire an equity interest against the compensation (through redemption of equity interest or part thereof from a company member), in an unencumbered transaction (based on the gift), through compulsory redemption of equity interest of a deceased member (if a company has this right under its instrument of incorporation), upon exit of a company member, upon exclusion of a company member and following a status change. The paper concentrates on acquisition of an equity interest against a compensation paid to a company member and through the compulsory redemption of equity from the heirs of a deceased member. Acquisition of an equity interest against the payment of a compensation exists in a case of an exit of a company member based on justifiable reasons. However, the acquisition in that case is a consequence of an exit of a member and not of the company’s intent.